Biological properties of a novel solution based on silver nanoclusters for arresting dentin caries - Molina, Gustavo Fabián (2024)
Objectives: To test the biological properties of a novel non-restorative treatmentmethod for arresting dentin caries based on silver nanoclusters (AgNCls)synthesized in polymethacrylic acid (PMAA).Methods: Synthesis of AgNCls was performed by photoreduction of AgNO3 inPMAA with 355 nm/wavelength light. AgNCls/PMAA was characterized byabsorption/fluorescence spectroscopy and optical and atomic force microscopy.The stability of the clusters in an aerated PMAA solution was evaluated by meansof fluorescence spectroscopy. Cytotoxicity was assessed using the MTT assayand antibacterial effect was determined for minimum inhibitory concentration(MIC), minimum bactericidal concentration (MBC) and colony forming (CFU) ofStreptococcus mutans (S. mutans) and Lactobacillus acidophilus (L. acidophilus).38% Silver Diammine Fluoride (SDF) was used for the control groups.Results: Chemical and structural identity of the clusters did not change within 9months; Cell viability of 92%–89% was found after 24–48 h respectively. MICand MBC were determined from 1:16 and 1:8 dilutions, respectively. Log CFUcounts of S. mutans, and L. acidophilus treated with AgNCls/PMAA (3.4 ppm ofsilver) were significantly lower than in the control groups and even lower thanwhen the same bacterial strains were treated with SDF (15,525 ppm of silver).Conclusions: AgNCls/PMAA presented chemical stability, acceptablecytotoxicity, and a potential antibacterial effect for strains associated withcaries lesions at very low concentrations of silver.